THE POSITION OF TEACHERS CAN NOT BE REPLACED BY INSTRUCTIONAL MEDIA - Yos Sudarman (International Conference on Languages and Arts, 2016)
The teacher's role is very important during the learning process, especially in learning Indonesian. Teachers are required to master the rules of Indonesian well and correctly and creatively during the learning takes place. It is intended that the student has an appeal and a strong interest to bahasa skills. If the students' interest in learning and communicating acceleration has occurred, then the permanent teachers took part as an innovative container during the learning takes place. Therefore, teachers should have the power concept as a prop during the learning power and remain creative in developing learning strategies Indonesian. Teacher's creativity in learning activities vary depending on the level of language skills, namely listening, speaking, reading, and writing. Therefore, teachers should have the power concept as the power prop for learning and creative in developing Indonesian learning strategies in order to create an integrative learning. necessary revolution integrative learning strategies against Indonesian skills to enable the acceleration in Indonesian language learning communicative and interactive. The teacher needs to integrate as well as the harmony and balance between the literary aspects and aspects of language that in the four language skills. It also requires a coherent collaboration between teachers and students and teachers with parents.